2012
DOI: 10.1185/03007995.2012.708653
|View full text |Cite
|
Sign up to set email alerts
|

Why is warfarin underused for stroke prevention in atrial fibrillation? A detailed review of electronic medical records

Abstract: Many patients with AF and moderate-to-high risk of stroke are not treated with warfarin, and reasons for not using warfarin could not always be identified in patient records. Among patients with documented reasons, risk of bleeding (risk of fall or recent bleeding) was the most common category.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

2
13
0
1

Year Published

2015
2015
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 24 publications
(16 citation statements)
references
References 35 publications
2
13
0
1
Order By: Relevance
“…Contraindications have often been cited as a reason for not prescribing anticoagulants. 17,[19][20][21] However, this analysis suggests that contraindications do not stop clinicians from prescribing; this agrees with findings from studies in the US and Europe. [22][23][24] It is unclear why many patients with AF without contraindications are not prescribed anticoagulants, while patients with contraindications are.…”
Section: Comparison With Existing Literaturesupporting
confidence: 87%
“…Contraindications have often been cited as a reason for not prescribing anticoagulants. 17,[19][20][21] However, this analysis suggests that contraindications do not stop clinicians from prescribing; this agrees with findings from studies in the US and Europe. [22][23][24] It is unclear why many patients with AF without contraindications are not prescribed anticoagulants, while patients with contraindications are.…”
Section: Comparison With Existing Literaturesupporting
confidence: 87%
“…Among them, 41% of patients did not receive warfarin despite guidelines recommending anticoagulation therapy for such subjects [10]. Rosenman et al found that only 49% of high-risk patients received warfarin through chart review [11]. Although direct comparison of our study with the previous studies is not feasible, due to the differences in the definitions of WU along with study subjects and design, WU is a common and persistent issue in current clinical practice.…”
Section: Discussionmentioning
confidence: 84%
“…Despite the strong evidence of benefits, a number of studies have shown that warfarin has been underused among patients who appear to be appropriate candidates for it [10][11][12][13][14][15][16][17][18][19][20][21][22][23][24][25]. A systematic review was conducted with nine studies that utilized CHADS2 !2 to identify high-risk patients for stroke.…”
mentioning
confidence: 99%
“…In spite of ample evidence that Vitamin K antagonists reduce the risk of stroke and disability [13], anticoagulation has historically been underutilized in the very elderly population[14]. An increased risk of bleeding in this patient sub-group as well as frequent falls have been commonly cited reasons for avoiding anticoagulation [15]. …”
Section: Discussionmentioning
confidence: 99%